Amplified expression of the tag+ and alkA+ genes in Escherichia coli: identification of gene products and effects on alkylation resistance. - Kaasen, I (1986)
We have constructed plasmids which overproduce the tag and alkA gene products of Escherichia coli, i.e., 3-methyladenine DNA glycosylases I and II. The tag and alkA gene products were identified radiochemically in maxi- or minicells as polypeptides of 21 and 30 kilodaltons, respectively, which are consistent with the gel filtration molecular weights of the enzyme activities, thus confirming the identity of the cloned genes. High expression of the tag+-coded glycosylase almost completely suppressed the alkylation sensitivity of alkA mutants, indicating that high levels of 3-methyladenine DNA glycosylase I will eliminate the need for 3-methyladenine DNA glycosylase II in repair of alkylated DNA. Furthermore, overproduction of the alkA+-coded glycosylase greatly sensitizes wild-type cells to alkylation, suggesting that only a limited expression of this enzyme will allow efficient DNA repair.